Pancasila as the Ethical Foundation of Nation and State in the Digital Era - kamil, Muhammad Farhan; Evriano, Wahyu Reygil; Armi, Meily (Jurnal Edukasi Terkini, 2025)
Abstrak Purpose-This study analyzes the role of Pancasila as an ethical foundation for nationhood and citizenship in Indonesia amid the rapid transformations brought by the digital age. The research seeks to explain how Pancasila’s core values can guide civic ethics in an era marked by intensified technological influence on social interaction, political communication, and cultural identity. Research Methodology/Design/Approach-Using a qualitative approach with descriptive analysis, the study examines the application of Pancasila within the domains of digital citizenship education, social media behavior, and public policy frameworks. Data were synthesized from document analysis, observations of digital civic practices, and relevant academic literature. Findings – The results reveal that Pancasila remains highly relevant as a normative compass for addressing digital-era challenges, particularly ethical degradation, polarization, and misinformation. The study finds that strengthening Pancasila-based ethics can be implemented through three key strategies: (1) integration of Pancasila values in digital citizenship education, (2) development of ethical guidelines for responsible social media engagement, and (3) formulation of public policies that reinforce democratic values and social cohesion. However, challenges persist, including inconsistent digital literacy, algorithm-driven bias, and the weakening of communal norms in online interactions. Originality/Value-This study contributes to contemporary civic education discourse by offering a conceptual model for revitalizing Pancasila ethics in digital society. It highlights the need for collaborative efforts between government, educational institutions, and civil society to develop context-sensitive interventions capable of nurturing ethical and responsible citizenship in an increasingly digitalized Indonesia.